Criminal law and human rights in the Caribbean: a paradoxical relationship - Affonso, Timothy A. (The Palgrave handbook of Caribbean criminology, 2024)
Human rights in the Commonwealth Caribbean are thematically linked to international standards. The framework for human rights takes its lead from topical issues globally. Unfortunately, the rights’ discussion in a criminal law context in the Caribbean is too often slanted. This means that there is a tendency to see the status quo as acceptable in the Caribbean with the result that there is a gap between human rights principles and what actually takes place in the justice system across the region. This chapter will explore the right to a fair trial with particular reference to the law related to delay. In looking at this issue, one will see the close link between this area of law and human rights standards.